Profitabilitas dan Leverage terhadap Nilai Perusahaan pada Perusahaan Infrastruktur yang Terdaftar di Bursa Efek Indonesia (BEI) Tahun 2019-2023 - Riayu, Annisaa’ Putri; Dewi, Aminar Sutra (ARZUSIN, 2026)
This study is motivated by the importance of firm value as an indicator of investor confidence in a company’s performance and prospects, particularly in the infrastructure sector, which plays a strategic role in national development. This study aims to analyze the effect of profitability and leverage on firm value in infrastructure companies listed on the Indonesia Stock Exchange for the 2019–2023 period. This study used a quantitative approach with a causal-associative design. The research data consisted of secondary data obtained from companies’ financial statements and annual reports. The sample was determined using purposive sampling based on specific criteria, resulting in 80 observational data. Firm value was measured using Price to Book Value (PBV), profitability was measured using Return on Equity (ROE), while leverage was measured using the debt ratio. The data were analyzed using panel data regression with the assistance of EViews 12. The results show that profitability has a positive and significant effect on firm value. Leverage was also proven to have a significant effect on firm value. These findings confirm that a company’s ability to generate profits and manage its debt structure is an important factor in increasing firm value. This study contributes to the development of financial management studies, particularly regarding the determinants of firm value in the infrastructure sector. The practical implications of this study may serve as a consideration for company management in formulating financial policies and for investors in making investment decisions based on profitability performance and funding structure.